Prenatal phenotype features and genetic etiology of the Williams-Beuren syndrome and literature review - Wang, Yunan; Liu, Chang; Hu, Rong; Geng, Juan; Lu, Jian; Zhao, Xianzhe; Xiong, Ying; Wu, Jing; Yin, Aihua (Frontiers in Pediatrics, 2023)
Objective To share our experience on prenatal diagnosis of Williams-Beuren syndrome(WBS) and to improve the awareness, diagnosis, and intrauterine monitoring of the fetuses of this disease. Methods The study retrospectively evaluated 14 cases of WBS diagnosed prenatally by single nucleotide polymorphism array (SNP-array). Clinical data from these cases were systematically reviewed, including maternal demographics, indications for invasive prenatal diagnosis, ultrasound findings, SNP-array results, trio-medical exome sequencing (Trio-MES) results, QF-PCR results, pregnancy outcomes and follow-ups. Results A total of 14 fetuses were diagnosed with WBS and their prenatal phenotypes were assessed retrospectively. In our case series, the most common ultrasound features were intrauterine growth retardation (IUGR), congenital cardiovascular defects, abnormal fetal placental doppler indices, thickened nuchal translucency(NT) and polyhydramnios. Other less common ultrasound features include fetal hydrops, hydroderma, bilateral pleural effusion, subependymal cysts, etc. Parental chromosome analysis was performed in seven pairs of parents, and all the deletions on chromosome 7q11.23 were de novo. Conclusion Prenatal ultrasound features of WBS cases are highly variable, with IUGR, cardiovascular abnormalities and abnormal fetal placental doppler indices, being the most common intrauterine phenotypes. Our case series expand the intrauterine phenotypes of WBS, including cardiovascular abnormalities right aortic arch(RAA) combined with persistent right umbilical vein(PRUV) and elevated the ratio of end-systolic peak flow velocity to end-diastonic peak flow velocity(S/D). In the meantime, with the decrease in the cost of the next-generation sequencing, the method may become widely used in prenatal diagnosis in the near future.